2014
DOI: 10.1111/pace.12348
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy Plus Coupled Pacing Improves Acutely Myocardial Function in Heart Failure Patients

Abstract: In sinus rhythm HF patients, acute CP application in addition to CRT decreases HR and contributes to myocardial contractility and CO improvement without deleterious impact on ventricular synchronicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In patients with heart failure, cardiac resynchronization therapy (CRT) for 6 months was associated with reduced end‐diastolic and end‐systolic volume, reduced LV mass, increased ejection fraction, reduced mitral regurgitant blood flow, and improved myocardial performance index as compared with controls [5–8].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with heart failure, cardiac resynchronization therapy (CRT) for 6 months was associated with reduced end‐diastolic and end‐systolic volume, reduced LV mass, increased ejection fraction, reduced mitral regurgitant blood flow, and improved myocardial performance index as compared with controls [5–8].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies evaluated the use of coupled pacing in addition to cardiac resynchronisation therapy in heart failure patients with mechanical dyssynchrony 66,67. A further increase in contractility and EF was seen along with a decrease in pulse rate without disrupting the synchronisation properties of CRT.…”
mentioning
confidence: 99%
“…A further increase in contractility and EF was seen along with a decrease in pulse rate without disrupting the synchronisation properties of CRT. While Stegeman et al concluded that this drop in pulse rate reduced the haemodynamic benefit of paired pacing, Brémont et al suggested that the heart rate reduction could have an additional beneficial effect because of increased time for ventricular filling and reduced myocardial work 66,67.…”
mentioning
confidence: 99%